The Rational Limits of the Criminalization of Abortion – Legal and Social Consequences of the Restrictive Approach - Olga Sitarz; Michał Grudecki (Medicine, Law & Society, 2022)
This article aims to analyze a proposed amendment of 2021 to the Polish Criminal Code relating to abortion. The starting point for the considered legal solutions is the equalization of criminal law protection of human life before and after birth. This means that a termination of pregnancy is to be regarded as homicide, with all its attendant consequences. This article analyzes the legal implications arising from the proposed amendments both in relation to pregnant women and other persons (doctors, relatives and even employers of pregnant women). The far-reaching repressiveness of the future anti-abortion law that is rarely found in the modern world is demonstrated. The analysis is complemented with an attempt to diagnose the social consequences of the proposed amendments using historical and criminological texts concerning such situations in the past, as well as on the basis of sociological observations of current social trends. The authors believe that the proposed law will prove to be ineffective, and children (including unborn ones) will be maleficiaries rather than beneficiaries of the amendments in question.
Keywords: abortion, homicide, pro-life, termination of pregnancy, draft amendment